Research Progress on the Composition of Bacteriophages and the Effects on Quality Formation in Fermented Foods - Jiaqi LIU; Menglu YANG; Yuli HUANG; Mengting LIU; Lihong GE; Nan ZHAO (Shipin gongye ke-ji)
Fermented foods, whose components are transformed through a controlled microbial fermentation process, are an important part of people's daily diets due to their pleasurable flavors and probiotic-rich properties. However, the microbial composition of fermented foods is highly complex. Studies focusing solely on bacteria and fungi are insufficient to fully elucidate the multifaceted quality formation mechanisms of fermented foods, necessitating investigations into understudied microbial groups such as archaea and bacteriophages. Therefore, in recent years, researchers have gradually shifted their focus to phages to develop systematic biocontrol strategies. Phages are detected in diverse fermented foods, and studies demonstrated that environmental stressors—such as pH fluctuations, ionic strength, and microbial metabolites (e.g., organic acids)—alters phage life cycles through quorum sensing systems. These perturbations induces the lytic-lysogenic switch in temperate phages, activating virulent phenotypes. Phages enable the formation of final product quality through two key mechanisms: lysing core or pathogenic microorganisms, and genetically modulating acid-production metabolism in core microbial communities. This review summarizes the composition of phages in fermented foods, including Siphoviridae, Myoviridae and Podoviridae. Additionally, it provides an overview of the mechanisms by which phages affect host metabolism by lysing the host or modulating their metabolic pathways, thus indirectly affecting the fermentation process and ultimately leading to an enhancement or deterioration of the product quality (sensory, nutritional, safety), aiming to provide scientific guidance for improving the controllability of the quality of fermented foods.